COVID-19: Public support to handle economic challenges - Mohammad Hidayaturrahman; Edy Purwanto (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2020)
COVID-19, which has become a world pandemic, has hit the economic sectors of countries in the world, including Indonesia. Indonesia's economic growth is predicted to be only around 2% or even 0%. This research was conducted to analyze how public support for government efforts to deal with COVID-19 and describe how the economic challenges faced. This research uses descriptive qualitative method by collecting data through in-depth interviews with several informants relating to public support for government efforts. Data collection is also done by searching for related documents online. From the research conducted, the government has the opportunity and strength to carry out initiatives to deal with COVID-19. Administrative support, regional government, business, political parties, including the opposition, and the people are tremendous. The problem is, the government's efforts and scenarios are not visible to anticipate the economic threats that are already in sight. This research wants to uncover the power of government in the form of public support in dealing with COVID-19, and remind the government, the economic challenges faced with the existence of COVID-19.